Investigation of Handwriting Changes of a Subject who Committed Suicide by Drinking Antifreeze - Kömür, İlhami; Şahin, Esat; Saltı, Ersen; Seçkin, Çetin; Baklacıoğlu, Ferruh; Özbay, Işıl; Üner, Hüseyin Bülent (The Bulletin of Legal Medicine, 2015)
Although forensic autopsy was performed on the subject, who was found dead in his car, the reason of dead could not be identified. The body was found in his car with an antifreeze bottle near to him and with a suicide note telling that the subject committed suicide by drinking the antifreeze. In order to confirm the reason origin of the dead, prosecution office want to determine whether the suicide note was in fact written by the subject. The handwriting samples and the diary obtained from the scene were sent to The Council of Forensic Medicine Forensic Document Examination Laboratory for comparison.In this study, we aim to present a subject who committed suicide by drinking antifreeze (ethylene glycol) and noted what he feels until he looses his conscious. By investigating the impact of ethylene glycol intake on handwriting changes, we would like to show the contribution of forensic document examination to determination of reason of dead.Keywords: Ethylene glycol. Suicide, Handwriting, Questioned Document
Keywords: ethylene glycol; suicide; handwriting; questioned document